(untitled) (CIPEEX, 2025)
This experience report presents reflections on the process of guiding undergraduate theses (TCC) in the Psychology program at UniEvangélica, based on the trajectory developed with different groups of students over recent semesters. Thesis supervision has been configured not only as the fulfillment of a curricular requirement but also as a privileged educational space where research, scientific production, and the development of professional competencies converge. Throughout this process, recurrent challenges were identified, such as the proper delimitation of research topics, mastery of scientific methodologies, academic writing, and the critical use of theoretical references. In response, strategies were adopted that prioritized the strengthening of students’ autonomy, the encouragement of critical thinking, and the appreciation of the learning process rather than merely the final product. Along this path, students produced works addressing socially relevant themes such as gender-based violence, mental health, inclusive education, and alcoholism in rural communities, demonstrating the potential of undergraduate theses as instruments for dialogue between university and society. The results of this experience indicate that thesis supervision, when conducted in a humanized and collaborative manner, contributes to the integration of future psychologists into the field of research and professional practice, while fostering social responsibility, ethical sensitivity, and a commitment to transforming reality.